Pembuatan dan Uji Nilai HU Jaringan Tulang Buatan Berbahan Dasar Cangkang Telur - Eunike Yusmaliani; Astuty, Sri Dewi; Purwanto; Dewang, Syamsir; Bannu; Ibrahim, Ajeng Anggreny; Pratiwi, Ayu Hardianti (Universitas Islam Negeri Alauddin Makassar, 2025)
Performance evaluation of diagnostic radiology modalities strongly supports the quality of radiation and images for diagnosis. This test requires certain materials as a substitute for human objects to avoid excessive radiation. Phantom as one of the object replacement media has been directed according to the characteristics of the tissue. This study aims to obtain the radiation response of artificial bone tissue made from eggshells with the addition of rice bran, resin and catalyst, in 4 (four) mixture compositions. Test variations were carried out by changing the X-ray tube voltage (80 kV, 100 kV, 120 kV and 140 kV) to obtain CT-Scan images and analyzed using Radiant DICOM software. The results showed that the Hounsfield unit (HU) value of the artificial bone phantom corresponded to the HU value range of real bone organs, which is between 100 and 700 HU. This value affects the analysis of the resulting image resolution in the form of SNR and CNR values, in the range of (8.07-37.38) and (14.98-28.20), respectively. Conclusion Artificial bone tissue phantom made from eggshells and rice bran has the potential as a testing medium because it corresponds to the characteristics of human bones, especially in adulthood, and has the potential as a testing medium.